Cadmium coordination compounds with flexible ligand 1, 3-bis(1, 2, 4-triazol-1-yl)propane: Synthesis, structure and luminescent properties. (1st February 2020) - Smirnova, Ksenia S.; Lider, Elizaveta V.; Sukhikh, Taisiya S.; Berezin, Alexey S.; Potapov, Andrei S.
Graphical abstract: Five cadmium(II) coordination compounds with flexible 1, 3-bis(1, 2, 4-triazol-1-yl)propane (btrp) have been synthesized. The crystal structures of the complexes [Cd(btrp)(H2 O)2 (NO3 )2 ]n and [Cd2 (btrp)2 (DMF)2 (μ2 -Br)2 Br2 ] were determined, the latter reveals rare gauche – gauche conformation of btrp ligand. Luminescent properties of all complexes have been studied in comparison with free btrp. Abstract: Six new cadmium coordination compounds with flexible 1, 3-bis(1, 2, 4-triazol-1-yl)propane (btrp) ligand, [Cd(btrp)(H2 O)2 (NO3 )2 ]n (1 ), [Cd(btrp)2 (NO3 )2 ]·H2 O (2 ), [Cd(btrp)Hal2 ] (3 –5 ) (Hal = Cl, Br, I) and [Cd2 (btrp)2 (DMF)2 (μ2 -Br)2 Br2 ] (6 ) were synthesized. The crystal structures of the complexes 1 and 6 were determined. 1 has 1D polymeric structure while 6 is binuclear. The latter reveals rare gauche – gauche conformation of btrp ligand. Luminescent properties of 1 –6 in the solid state were studied in comparison with free btrp . The emission of the compounds corresponds to intraligand transitions, while the bands exhibit complicated shape that can be described by two Gauss functions.